1154. Safety and Efficacy of Ceftolozane/Tazobactam Plus Metronidazole Versus Meropenem in Pediatric Participants With Complicated Intra-abdominal Infection: A Phase 2, Randomized Clinical Trial. (4th December 2021) - Jackson, Carl-Christian A; Newland, Jason; Dementieva, Natalia; Lonchar, Julia; Su, Feng-Hsiu; Huntington, Jennifer A; Bensaci, Mekki; Popejoy, Myra W; Johnson, Matthew G; De Anda, Carisa S; Rhee, Elizabeth G; Bruno, Christopher
Abstract: Background: Ceftolozane/tazobactam (C/T), a cephalosporin–β-lactamase inhibitor combination, is approved for treatment of complicated urinary tract infections, complicated intra-abdominal infections (cIAI), and nosocomial pneumonia in adults. Safety and efficacy of C/T in pediatric participants with cIAI was assessed. Methods: This phase 2 study (NCT03217136) compared C/T + metronidazole (MTZ) with meropenem (MEM) for treatment of cIAI. Age- and weight-adjusted dosing is summarized in Table 1. The primary objective was to evaluate the safety and tolerability of C/T + MTZ compared with MEM. A key secondary endpoint was clinical cure at end of treatment (EOT) and test of cure (TOC). Table 1. Summary of Dosing and Pharmacokinetic Sampling Schedule by Age Cohort Results: A total of 94 participants were randomized 3:1; 91 were treated with C/T + MTZ (n=70) or MEM (n=21) comprising the modified intent-to-treat (MITT) population. The clinically evaluable population included 78 participants at EOT (C/T + MTZ, n=59; MEM, n=19) and 77 participants at TOC (C/T + MTZ, n=58; MEM, n=19). The most common diagnosis and pathogen in the MITT population were complicated appendicitis (C/T + MTZ, 91.4%; MEM, 100%) and Escherichia coli (C/T + MTZ, 67.1%; MEM, 61.9%). The mean (SD) intravenous therapy/overall treatment duration was 6.4 (2.8)/9.3 (3.6) days and 5.8 (1.8)/9.0 (3.2) days for C/T + MTZ and MEM, respectively. In total, ≥1 adverse events (AE) occurred in 80.0% and 61.9% of participants receiving C/T + MTZ and MEM, respectively (Table 2), of which 18.6% and 14.3% were considered drug related. Serious AE occurred in 11.4% (8/70) and 0% (0/21) of participants receiving C/T + MTZ and MEM, respectively; none were considered drug related. No drug-related study drug discontinuations occurred. In the MITT population, rates of clinical cure for C/T + MTZ and MEM at EOT were 80.0% and 95.2%, and at TOC were 80.0% and 100%, respectively (Figure 1); 6 of the 14 failures for C/T + MTZ were indeterminate responses scored as endpoint failures per protocol. In the clinically evaluable (CE) population, rates of clinical cure for C/T + MTZ and MEM were 89.8% and 100% at EOT, and 89.7% and 100% at TOC, respectively (Figure 1). Conclusion: C/T + MTZ was well tolerated in pediatric participants with cIAI, and rates of clinical success were high with C/T treatment. C/T is a promising new treatment option for children with cIAI. Disclosures: Carl-Christian A. Jackson, MD, Merck & Co. Inc. (Shareholder) Julia Lonchar, MSc, Merck Sharp & Dohme Corp. (Employee, Shareholder) Feng-Hsiu Su, MPH, MBA, Merck Sharp & Dohme Corp. (Employee, Shareholder) Jennifer A. Huntington, PharmD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee) Mekki Bensaci, PhD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee) Myra W. Popejoy, PharmD, Merck Sharp & Dohme Corp. (Employee) Matthew G. Johnson, MD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee) Carisa S. De Anda, PharmD, Merck Sharp & Dohme Corp. (Employee, Shareholder) Elizabeth G. Rhee, MD, Merck Sharp & Dohme Corp (Employee, Shareholder) Christopher Bruno, MD, Merck Sharp & Dohme Corp., a subsidiary of Merck & Co., Inc., Kenilworth, NJ, USA (Employee)